2019
DOI: 10.3390/genes10100744
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Clinical Characteristics of TECTA-Associated Autosomal Dominant Hearing Loss

Abstract: TECTA is well known as a causative gene for autosomal dominant mid-frequency hearing loss observed in various populations. In this study, we performed next-generation sequencing analysis of a large Japanese hearing loss cohort, including eight hundred and twelve (812) subjects from unrelated autosomal dominant hearing loss families, to estimate the prevalence and phenotype-genotype correlations in patients with TECTA mutations. The prevalence of TECTA mutations in Japanese autosomal dominant sensorineural hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
(50 reference statements)
3
20
0
Order By: Relevance
“…The frequency of MYO6-associated hearing loss was 2.40% in the Japanese AD hearing loss patients. This frequency is compatible with our previous study (2.6%; 7/266) [20] and is lower than the most frequent ADSNHL gene (6.6% for KCNQ4 [26]) but comparable with other ADSNHL genes, such as 3.2% for TECTA [27], 2.5% for POU4F3 [28], and 2.5% for WFS1 [29]. Therefore, MYO6 is considered an important causative gene for Japanese patients with ADSNHL.…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of MYO6-associated hearing loss was 2.40% in the Japanese AD hearing loss patients. This frequency is compatible with our previous study (2.6%; 7/266) [20] and is lower than the most frequent ADSNHL gene (6.6% for KCNQ4 [26]) but comparable with other ADSNHL genes, such as 3.2% for TECTA [27], 2.5% for POU4F3 [28], and 2.5% for WFS1 [29]. Therefore, MYO6 is considered an important causative gene for Japanese patients with ADSNHL.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, vWFD domains containing the multimerization consensus site CGLC are essential for the multimer assembly of proteins expressed in the tectorial membrane (like α-tectorin, otogelin or otogelin-like protein) to form a lament and higher order structures. Although little is known about these domains in OTOGL, mutations in the vWFDs of TECTA have been clearly connected with hearing impairment [37,44]. Moreover, the shape of the audiometric curve observed in our proband is almost identical to the audiogram obtained from the compound heterozygous patient carrying mutations p.Gln520* and p.Arg925* reported by Bonnet et al [42].…”
Section: Discussionsupporting
confidence: 83%
“…Missense mutations in different Tecta domains are known to cause different phenotypes with distinct changes in the structure of the tectorial membrane. Mutations in the zona pellucida domain cause mid-frequency HL with a typical U-shaped or shallow U-shaped audiogram, whereas mutations in the zonadhesin-like domain comprising vWFD1, vWFD2 and trypsin inhibitor-like (TIL) repeats lead to high-frequency HL[35,37]. Our results are in agreement with the ndings of previous studies: four of our variants (p.Gly1858Glu,…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Etiological studies have shown that genetic causes are the most common etiology of deafness, and approximately two-thirds of congenital/early-onset sensorineural hearing loss in developed countries is estimated to be due to genetic causes (Morton and Nance 2006). Recent studies have indicated that a significant portion of late-onset hearing loss is also due to genetic causes (Kitano et al 2017;Kobayashi et al 2018;Shinagawa et al 2020a;Yasukawa et al 2019;Oka et al 2020;Miyajima et al 2020). A series of etiological studies has demonstrated genetic disorders to be a common cause of all types of sensorineural hearing loss, but there has been no detailed genetic epidemiological data covering a wide range of ages.…”
Section: Genetic Epidemiology Based On Genetic Testingmentioning
confidence: 99%